Comprehensive Analysis of Sulfated Flavonoids in Eclipta prostrata for Quality Evaluation - Sato, Ryunosuke; Nishidono, Yuto; Tanaka, Ken (Molecules (Basel, Switzerland), 2024)
Eclipta prostrata (Asteraceae) is employed as a hemostatic agent in many traditional medicines, owing to its sulfated flavonoid content. In this study, we obtained crude drug samples from three provinces collected in different years and analyzed their sulfated flavonoid contents using liquid chromatography–mass spectrometry (LC–MS) for quality evaluation. Because sulfated flavonoids are unstable and difficult to isolate from extracts, this study first synthesized a variety of sulfated flavonoids and accumulated spectral data in order to identify the compounds in E. prostrata. The LC–MS analysis of six crude drug samples revealed the presence of luteolin 7-sulfate, apigenin 7-sulfate, diosmetin 7-sulfate, and diosmetin 3′-sulfate. The samples without luteolin 3′-sulfate featured high apigenin 7-sulfate content. Although the samples were collected from the same locality, their compositions differed depending on the year of collection. Further, they were classified according to three patterns: (1) samples with luteolin 7-sulfate as the main component, (2) samples with apigenin 7-sulfate as the main component, and (3) samples with relatively high diosmetin sulfate content. Luteolin 7-sulfate typically exhibits relatively high erythrocyte aggregation efficiency and fibrinogen aggregation rate. These results demonstrate that the analysis of sulfated flavonoids is beneficial for the quality evaluation of E. prostrata for hemostatic applications.